The Courtships of Lancaster County: Becoming Bea - Book 4 - Gould, Leslie, 1962- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2014)
"Ben and Bea have always irritated each other. But when their friends push them together, can they cease bickering long enough to fall in love?"--
Keywords: Interpersonal attraction; Fiction; Amish -- Fiction; Lancaster County (Pa.); Fiction; Christian fiction; Romance fiction; Christian fiction; Romance fiction